1999
DOI: 10.1046/j.1365-3180.1999.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed seeds in long‐term dryland tillage and cropping system plots

Abstract: Successful crop production depends on effective weed control. Weed seedbanks were determined after 12 years of dryland cropping with winter wheat and grain sorghum under different tillage methods (no‐ and stubble mulch) and cropping sequences. Seeds of 12 species were detected. Amaranthus retroflexus was most abundant, but seed numbers were similar under all conditions. Portulaca oleracea, Panicum capillare, Setaria viridis and Sorghum halepense seed numbers differed because of some factors, with those for P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Inclusion of fallow in our study reduced weed densities below that of monoculture winter wheat but weed densities remained similar to those of winter wheat-canola or winter wheat-flax (Table 2). Hume (1991) and Unger et al (1999) documented lower weed densities in crop-fallow than in continuous crop rotations.…”
Section: To 4)mentioning
confidence: 95%
See 1 more Smart Citation
“…Inclusion of fallow in our study reduced weed densities below that of monoculture winter wheat but weed densities remained similar to those of winter wheat-canola or winter wheat-flax (Table 2). Hume (1991) and Unger et al (1999) documented lower weed densities in crop-fallow than in continuous crop rotations.…”
Section: To 4)mentioning
confidence: 95%
“…1b). Redroot pigweed has previously been reported to increase (Buhler 1992), remain unchanged (Unger et al 1999), and Table 1 for species code. The proportion of the total variation accounted for by axes one and two was 96 and 4, 89 and 11, and 99 and 1% for the May, June, and October assessment dates, respectively.…”
Section: Species Association With Tillagementioning
confidence: 99%
“…because of high fecundity and seed longevity (e.g. Schweizer and Zimdahl 1984;Schweizer et al 1988;Cavers and Benoit 1989;Cardina et al 1991;Ball 1992;Forcella et al 1992;Mohler and Callaway 1995;Mulugeta and Stoltenberg 1997a, b;Hoffman et al 1998;Schweizer et al 1998;Unger et al 1999;Bàrberi and Lo Cascio 2001). In a survey of 50 corn fields in Colorado, Schweizer et al (1998) found seed banks of A. retroflexus, ranging in size from 200 to 89 460 seeds m -2 , on 90% of the fields.…”
Section: Reproductionmentioning
confidence: 99%
“…Crop rotation improves soil fertility, increases soil organic matter, reduces disease and weed infestations, and causes yield increases that are sometimes greater than can be explained by all of the above benefits (Bullock 1992;Huang et al 2002). The most successful crop rotations for weed management have been diverse rotations that include forage crops or rotating fall-seeded crops with spring-seeded crops (Pavlychenko 1942;Entz et al 1995;Ominski et al 1999;Unger et al 1999). These are rotations where the crop life cycles do not always match the weed life cycle (Liebman and Dyck 1993;Karlen et al 1994;Unger et al 1999;Blackshaw et al 2001).…”
Section: Mots Clésmentioning
confidence: 99%
“…The most successful crop rotations for weed management have been diverse rotations that include forage crops or rotating fall-seeded crops with spring-seeded crops (Pavlychenko 1942;Entz et al 1995;Ominski et al 1999;Unger et al 1999). These are rotations where the crop life cycles do not always match the weed life cycle (Liebman and Dyck 1993;Karlen et al 1994;Unger et al 1999;Blackshaw et al 2001). In the past, the economy of western Canada was geared to annual cereal production in grain-fallow or grain-grain-fallow systems.…”
Section: Mots Clésmentioning
confidence: 99%